Development of compressive-shear test rig for polymeric foam material behavior - Mohd Ruzaimi, MatRejab; Kumaran, Kadirgama; Muhamad, Mat Noor; Mohd Shahrir, Mohd Sani; A.Alias (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.